الطلاق في إقليم كردستان العراق : أسبابه وآثاره وحلوله في ضوء الشريعة الإسلامية - إسماعيل، أردوان مصطفى (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Divorce is regarded as a social problem that occurs in every society and the Iraqi Kurdistan Region is no exception to that. The rate of divorce has significantly increased in recent years due to social, economic, political and technological changes that have occured in the Kurdish society. The Islamic Sharia fully realizes the adverse effects that follow from divorce, and hence characterizes divorce as the most detestable Halal act. So Islam makes divorce permissible only when it is a blessing for husband and wife in case it becomes impossible for them to live together. This research consists of an introductory chapter and two sections to study the concept or definition of divorce, its verdict, the wisdom behind its legalization and its reasons in Iraqi Kurdistan Region. It also shows the effects of divorce, the ways to prevent it, and its remedies in the light of the Islamic Sharia. The researcher has adopted inductive, descriptive and analytical methods that included observation and interviews with people that have much to do with the subject matter of the research. It shows that a variety of social, economic, technological and legal reasons contribute to divorce, and divorce in turn brings about a whole host of psychological, economic, social and educational effects. The research clarified the role of different remedies like faithmotivated, moral and psychological ones as well as the returning of the wife and testifying of the divorce in the prevention of divorce. It also offers a variety of solutions to the problem from an Islamic perspective such as commitment to Islamic family policy, family counseling, guiding the media onto the righteous path as well as the good use of modern technology. The research concludes with a number of outcomes and recommendations, the most prominent of which are: the necessity of following the road map that Islam has drawn for divorce as a solution to a problem rather than a cause for creating problems. The establishment of marriage upon peace, love and compassion, the spouses' good treatment of each other, their compatibility, avoidance of spousal infidelity and intoxicants. The relatives should also avoid negative intervention in spousal life. It is also recommended that centers be opened for those who intend to get married, and last but least the incorporation of family education for soon -to- be married couples.